2018
DOI: 10.1016/j.nbt.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity and transfucosylation activity of GH29 α-l-fucosidases for enzymatic production of human milk oligosaccharides

Abstract: Human milk oligosaccharides (HMOs) constitute a unique family of bioactive lactose-based molecules present in human breast milk. HMOs are of major importance for infant health and development but also virtually absent from bovine milk used for infant formula. Among the HMOs, the fucosylated species are the most abundant. Transfucosylation catalysed by retaining α-l-fucosidases is a new route for manufacturing biomimetic HMOs. Seven α-l-fucosidases from glycosyl hydrolase family 29 were expressed, characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
115
2
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(145 citation statements)
references
References 54 publications
(146 reference statements)
3
115
2
3
Order By: Relevance
“…Furthermore, this new product could also be used as a standard when studying unknown enzymatic activities. In this context it is important to note, that a fucosyllactose other than the well-known 2'-FL and 3-FL was found as a translycosylation product in another study [14].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Furthermore, this new product could also be used as a standard when studying unknown enzymatic activities. In this context it is important to note, that a fucosyllactose other than the well-known 2'-FL and 3-FL was found as a translycosylation product in another study [14].…”
Section: Discussionmentioning
confidence: 81%
“…To our knowledge, there are no previous reports using free fucose as substrate for fucosyllactose production with any enzyme. However, there are α-fucosidases, Mfuc5 from a soil metagenome and FgFCO1 from Fusarium graminearum that have been shown to use xyloglucan as fucose donor [8,14,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the presence of an aromatic amino acid in the active site of the fucosidase from T. maritima induces a preference for monosaccharide acceptors, in particular, pNP‐monosaccharides. In fact, several monosaccharides, or their methyl, pNP, or allyl derivatives were used as acceptors in transfucosylation reactions . Ajisaka and Shirakabe and Murata et al.…”
Section: Employment Of Fucosidases In the Synthesis Of Fucosylated Olmentioning
confidence: 99%
“…Furthermore, transfucosylation reactions demand an activated donor substrate, which means that the fucose moiety that is to be transferred, must form a high energy bond with a good leaving group, so that the energy provided by cleaving this bond contributes to lowering the activation energy in the transglycosylation reaction, for example, mono or disaccharides, a methyl group, a nitrophenyl group, and even some halogens, such as F. By far, the most reported substrate in transfucosylation reactions is pNP‐Fuc . One reason is that many fucosidases recognize this compound as a substrate.…”
Section: Employment Of Fucosidases In the Synthesis Of Fucosylated Olmentioning
confidence: 99%